Determinants of Self-Care Behavior Based on the Theory of Planned Behavior in Hypertensive Patients: A Systematic Review - Dwi Puji Lestari; Abu Bakar; Herdina Mariyanti (Jurnal Ners, 2026)
Hypertension management largely depends on patients’ self-care behavior, including lifestyle modification and medication adherence. The Theory of Planned Behavior (TPB) offers a comprehensive framework to explain behavioral determinants influencing self-care practices. A systematic search was conducted in Scopus, PubMed, Web of Science, ScienceDirect, and ProQuest for English-language studies published between 2019 and 2025. Cross-sectional studies examining self-care behavior and determinants aligned with TPB constructs were included. Data were synthesized narratively following PRISMA guidelines, and methodological quality was assessed using the Joanna Briggs Institute checklist. Fifteen studies were included. Self-care behavior was generally suboptimal. Attitude (knowledge and beliefs), subjective norms (social and family support), and perceived behavioral control (self-efficacy) were consistently associated with self-care behavior, with perceived behavioral control emerging as the strongest determinant. TPB is a relevant framework for understanding self-care behavior in hypertensive patients. Interventions should focus on enhancing self-efficacy and social support alongside improving patient knowledge.